EXPRESSÃO DO RENDIMENTO DE GRÃOS EM LINHAGENS DE AVEIA BRANCA EM DIFERENTES ÉPOCAS DE APLICAÇÃO DE NITROGÊNIO - Cadore, Pablo R. B.; Valentini, Ana P. F.; Zambonato, Felipe; Gaviraghi, Fernando; Martins, João A. K.; Wagner, Juliano F.; Persich, Daiana L.; Battisti, Gabriel K.; Berto, Jorge; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo